2021
DOI: 10.1039/d1ra00175b
|View full text |Cite
|
Sign up to set email alerts
|

Lithium calix[4]arenes: structural studies and use in the ring opening polymerization of cyclic esters

Abstract: Novel Li-calix[n]arene complexes (n = 3, 4) having (–S–), (–SO–), (–SO2–), (–CH2OCH2–) or (–CH2–) bridges have been synthesized and fully characterized. Their catalytic activity in the ring opening polymerization of lactones has been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…37 The screening of 1−5 (Table 1; for M n,cal , PDIs, and TONs, see Table S1) revealed that under these conditions the lithium/ Chart 3. Literature Complexes I−III 9,35 aluminum-based complex, namely 5, could achieve higher activities when compared with the other complexes herein.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…37 The screening of 1−5 (Table 1; for M n,cal , PDIs, and TONs, see Table S1) revealed that under these conditions the lithium/ Chart 3. Literature Complexes I−III 9,35 aluminum-based complex, namely 5, could achieve higher activities when compared with the other complexes herein.…”
Section: Resultsmentioning
confidence: 80%
“…With the track record of lithium-based systems for the ring-opening polymerization (ROP) of cyclic esters in mind, ,,, the ability of the complexes herein to perform as catalysts in the ROP of ε-caprolactone (ε-CL), δ-valerolactone (δ-VL), and rac -lactide ( r -LA), in the presence of 1 equiv of benzyl alcohol (BnOH) per lithium, has been studied. Results are discussed versus reported calixarene complexes I – III (Chart ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations